Lagrangian flow measurements and observations of the 2015 Chilean tsunami in Ventura, CA - Nikos Kalligeris; Vassilios Skanavis; Sasan Tavakkol; Aykut Ayca; Hoda El Safty; Patrick Lynett; Costas Synolakis (Geophysical Research Letters)
Abstract Tsunami‐induced coastal currents are spectacular examples of nonlinear and chaotic phenomena. Due to their long periods, tsunamis transport substantial energy into coastal waters, and as this energy interacts with the ubiquitous irregularity of bathymetry, shear and turbulent features appear. The oscillatory character of a tsunami wave train leads to flow reversals, which in principle can spawn persistent turbulent coherent structures (e.g., large vortices or “whirlpools”) that can dominate damage and transport potential. However, no quantitative measurements exist to provide physical insight into this kind of turbulent variability, and no motion recordings are available to help elucidate how these vortical structures evolve and terminate. We report our measurements of currents in Ventura Harbor, California, generated by the 2015 Chilean M8.3 earthquake. We measured surface velocities using GPS drifters and image sequences of surface tracers deployed at a channel bifurcation, as the event unfolded. From the maps of the flow field, we find that a tsunami with a near‐shore amplitude of 30 cm at 6 m depth produced unexpectedly large currents up to 1.5 m/s, which is a fourfold increase over what simple linear scaling would suggest. Coherent turbulent structures appear throughout the event, across a wide range of scales, often generating the greatest local currents.